PERANCANGAN PETA ONLINE MENGGUNAKAN MAPSERVER UNTUK MEREALISASIKAN INFRASTRUKTUR DATA SPASIAL (IDS) SERTA SIMULASI PEMANFAATANNYA DALAM UPAYA MEMFASILITASI TUKAR GUNA DATA SPASIAL (Studi Kasus Analisis Wilayah Terdampak Banjir di Kota Singaraja) - I Wayan Krisna Eka Putra (Media Komunikasi Geografi, 2013)
This research aim to simulate the use of local SDI to geospatial data sharing about a case studyanalysis of flood area in Singaraja City. Design of SDI in this research using MapServer software, while theanalysis of flood area using ArcGIS software. The main data that used are map of the road, distribution of theschool, landuse, river and contour. The results of this research define a SDI that facilitates to user to accessgeospatial data that distributed in each of agency. The results of flood area are ( + 1.192.399 m2), rice field(+ 170.371 m2), moor (+ 40844 m2), garden ( + 326.404 m2), school (8 school), dan some of the roadnetwork.Keyword : SDI, geospatial data sharing, flood.